1993
DOI: 10.1262/jrd.39.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Calcium and Phosphorus Administrations on Secondary Sex Ratio in Pigs.

Abstract: When 19,025 sows were administered with a calcium (Ca) and phosphorus (P) preparation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Considerable folklore particularly in humans has arisen regarding preconception methods to manipulate animal sex ratio including suggestions that the ingestion of sweet foods will increase the chances of having a female, whereas the ingestion of sour foods will produce males. For exemple, in pigs, Toriumi et al (1993) reported on the effect of a Ca/P-enriched diet (2.15% Ca and 1.28% P) on the sex ratio; the male:female ratio for sows receiving a standard and enriched diet was 0.89 and 1.32, respectively. However, in theory, since the testes produce an equal number of X-and Y-bearing sperm, there should be an exactly equal number of males and females born in mammals.…”
Section: Factors Affecting Sex Ratiomentioning
confidence: 99%
“…Considerable folklore particularly in humans has arisen regarding preconception methods to manipulate animal sex ratio including suggestions that the ingestion of sweet foods will increase the chances of having a female, whereas the ingestion of sour foods will produce males. For exemple, in pigs, Toriumi et al (1993) reported on the effect of a Ca/P-enriched diet (2.15% Ca and 1.28% P) on the sex ratio; the male:female ratio for sows receiving a standard and enriched diet was 0.89 and 1.32, respectively. However, in theory, since the testes produce an equal number of X-and Y-bearing sperm, there should be an exactly equal number of males and females born in mammals.…”
Section: Factors Affecting Sex Ratiomentioning
confidence: 99%